Analisis Faktor Penyebab Putus Sekolah pada Siswa Sekolah Dasar: Studi Kasus di Desa Mola Bahari, Indonesia - Wahyuni, Anisa Sri; Fua, Jumarddin La; Rasmi, Rasmi (IAIN Kendari, 2024)
The phenomenon of elementary school dropout remains a serious concern in efforts to improve national education quality. This study aims to analyze the factors causing school dropout among children in Mola Bahari Village, Wangi-Wangi Selatan District, Wakatobi Regency. A qualitative approach was employed, using purposive sampling to select 15 school dropouts as main informants, supported by interviews with parents and community leaders. Data were collected through in-depth interviews, participant observation, and documentation, and analyzed using the Miles and Huberman model with validation through source, technique, and time triangulation. The findings identified three main factors causing school dropout: low learning interest, family economic limitations, and unsupportive social environments. These results highlight the need for a holistic, community-based approach to reduce school dropout rates. This study enriches the understanding of educational dynamics in coastal areas and provides an empirical basis for future intervention strategies.Keywords: School dropout, learning interest, family economy, social environment, elementary education